First-Episode Psychotic Patients Showed Longitudinal Brain Changes Using fMRI With an Emotional Auditory Paradigm - González-Vivas, Carlos; García-Martí, Gracián; Soldevila-Matías, Pau; Sanz-Requena, Roberto; Aguilar, Eduardo J.; Castro-Bleda, María José; Martí-Bonmatí, Luis; Sanjuan, Julio (Frontiers in Psychiatry, 2020)
Most previous longitudinal studies of functional magnetic resonance imaging (fMRI) in first-episode psychosis (FEP) using cognitive paradigm task, found an increased activation after antipsychotic medications. We designed an emotional auditory paradigm to explore brain activation during emotional and non-emotional words processing. This study aimed to analyze if longitudinal changes in brain fMRI BOLD activation is present in patients versus healthy controls. A group of FEP patients (n = 34) received clinical assessment and had a fMRI scan at baseline and follow-up (average, 25-month interval). During the fMRI scan, both emotional and non-emotional words were presented as a block design. Results were compared with a pair healthy control group (n = 13). Patients showed a decreased activation at follow-up fMRI in amygdala (F = 4.69; p = 0.04) and hippocampus (F = 5.03; p = 0.03) compared to controls. Middle frontal gyrus was the only area that showed a substantial increased activation in patients (F = 4.53; p = 0.04). A great heterogeneity in individual activation patterns was also found. These results support the relevance of the type of paradigm in neuroimaging for psychosis. This is, as far as we know, the first longitudinal study with an emotional auditory paradigm in FEP. Our results suggested that the amygdala and hippocampus play a key role in psychotic disease. More studies are needed to understand the heterogeneity of response at individual level.